UNIMAS students' spiritual qualities and learning styles - Chen, Sao Yong (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research raised spirituality in education from the research on Spirituality in Higher Education by Higher Education Research Institute (HERI), and integrates spiritual qualities with Kolb’s Learning Styles. Parallel with Malaysia Education Blueprint (MEB) 2015-2015 for Higher Education (MEB (HE)), a transformation of education is needed to create holistic students with balanced ethics and knowledge. 378 undergraduates were selected as research participants with cluster sampling from all faculties and centres in UNIMAS. A questionnaire combined with adapted College Students’ Beliefs and Values (CSBV) and Kolb Learning Style Inventory version 3.1 (KLSI 3.1) was used to measure participants’ spiritual qualities and learning styles. Majority of participants practice Ecumenical Worldview and are Convergers. There is a weak relationship between all spiritual qualities and learning styles. Spiritual Quest, Equanimity, and Charitable Involvement share a positive relationship with learning styles. Linguistics, Communication Studies and Cognitive Sciences students are Assimilators with most balanced spiritual qualities and are the second most frequent group of learners.